Finnish Subacromial Impingement Arthroscopy Controlled Trial (FIMPACT): a protocol for a randomised trial comparing arthroscopic subacromial decompression and diagnostic arthroscopy (placebo control), with an exercise therapy control, in the treatment of shoulder impingement syndrome. Issue 5 (6th June 2017) - Paavola, Mika; Malmivaara, Antti; Taimela, Simo; Kanto, Kari; Järvinen, Teppo LN
Abstract : Introduction: Arthroscopic subacromial decompression (ASD) is the most commonly performed surgical intervention for shoulder pain, yet evidence on its efficacy is limited. The rationale for the surgery rests on the tenet that symptom relief is achieved through decompression of the rotator cuff tendon passage. The primary objective of this superiority trial is to compare the efficacy of ASD versus diagnostic arthroscopy (DA) in patients with shoulder impingement syndrome (SIS), where DA differs only by the lack of subacromial decompression. A third group of supervised progressive exercise therapy (ET) will allow for pragmatic assessment of the relative benefits of surgical versus non-operative treatment strategies. Methods and Analysis: Finnish Subacromial Impingement Arthroscopy Controlled Trial is an ongoing multicentre, three-group randomised controlled study. We performed two-fold concealed allocation, first by randomising patients to surgical (ASD or DA) or conservative (ET) treatment in 2:1 ratio and then those allocated to surgery further to ASD or DA in 1:1 ratio. Our two primary outcomes are pain at rest and at arm activity, assessed using visual analogue scale (VAS). We will quantify the treatment effect as the difference between the groups in the change in the VAS scales with the associated 95% CI at 24 months. Our secondary outcomes are functional assessment (Constant score and Simple shoulder test), quality of life (15D and SF-36), patient satisfaction, proportions of responders and non-responders, reoperations/treatment conversions, all at 2 years post-randomisation, as well as adverse effects and complications. We recruited a total of 210 patients from three tertiary referral centres. We will conduct the primary analysis on the intention-to-treat basis. Ethics and Dissemination: The study was approved by the Institutional Review Board of the Pirkanmaa Hospital District and duly registered at ClinicalTrials.gov. The findings of this study will be disseminated widely through peer-reviewed publications and conference presentations. Trial registration number: NCT00428870; Pre-results.